Ascertainment of K Nutrient Availability Class for Maize by Several Methods - Marthen Pasang Sirappa; Peter Tandisau (JOURNAL OF TROPICAL SOILS, 2015)
Research was conducted in Gowa, South Sulawesi at dry land farmer during two years. The aims of the research was to get the best method in ascertainment of availability class of potassium (K) for maize in dry land. The research used a single location approach, which made some of K nutrient artificial. Result of this research indicated that K nutrients class which reached by several methods are: (1) by Cate-Nelson method : two class, ie low and high class, (2) by curve continue method: two until three classes, ie very low to moderate class, low and moderate, and low to high class; and (3) by analysis of variance modified method: three classes, ie low to high class. Ascertainment of K nutrient availability classes by modified analysis of variance method was the best methods compared to other methods. Critical level of K nutrient for maize according to modified analysis of variance method by several extractant is: 0.40 me K 100 g-1 for NH4OAc pH 4.8 extractant; 0.40 to 0.60 me K 100 g-1 for NH4OAc pH 7 extractant; 200-300 ppm K2O for Bray-1 extractant, and 215-250 ppm K2O for Olsen extractant. [How to Cite: Marthen PS and P Tandisau. 2015. Ascertainment of K Nutrient Availability Class for Maize by Several Methods. J Trop Soils 19: 21-27. Doi: 10.5400/jts.2015.20.1.21][Permalink/DOI: www.dx.doi.org/10.5400/jts.2015.20.1.21]